Review of The Existing Drainage Channel Development Method (Case Study: Semani Road Environment (Sentosa-Remaja-Ahmad Yani) - Norhayati, Norhayati; siregar, adde currie; Carlina , Evi (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
The purpose of this review study is to see the effectiveness of the method of implementing primary canals in the Semani environment (Sentosa-Remaja-Ahmad Yani) Management and Development of Drainage Systems that are Directly Connected to Rivers across Regency/City Areas and Provincial Strategic Areas. This condition shows the importance of handling drainage problems. Measurements use mechanical and manual, data collection is carried out in natural settings (natural conditions), primary data sources and data collection techniques involve more participant observation, in-depth interviews, and documentation. From the results of reviews and observations during practical work, I concluded that we can really learn the techniques and conditions for making good drainage. so that the desired results can be maximized. The benefit of this study review is that we know how effective the work of the Semani environmental drainage project (Sentosa-Remaja-Ahmad Yani) is. It is hoped that this will eliminate the problem of flooding in the area